Delayed sleep phase syndrome and bipolar disorder: Pathogenesis and available common biomarkers. (October 2018) - Talih, Farid; Gebara, Nour Y.; Andary, Farah S.; Mondello, Stefania; Kobeissy, Firas; Ferri, Raffaele
Summary: Circadian rhythm disturbances are common in bipolar affective disorder (BD). Delayed sleep-wake phase syndrome (DSWPD) is the most prevalent circadian rhythm sleep-wake disorder (CRSWDs) and is frequently observed in BD. It is unclear whether DSWPD in BD is an independent process or is a consequence of BD. In this hypothetical review, we discuss the overlap between BD and DSWPD and potential common biomarkers for DSWPD and BD. The review will include a discussion of the genetics of DSWPD and BD. Biomarkers elucidating the pathophysiological processes occurring in these two disorders may offer insight into the etiology and prognosis of both conditions.